EVALUASI PENERAPAN SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (STUDI PADA BIRO ORGANISASI SEKRETARIAT DAERAH PROVINSI SULAWESI TENGAH) - Palenga, Farida H. (Katalogis, 2017)
The purpose of this study was to reveal the results of the implementation evaluation of Performance Accountability System for Government Agencies (Sistem Akuntabilitas Kinerja Instansi Pemerintahan - SAKIP) at Organization Bureau of Central Sulawesi Regional Secretariat and to find out the inhibiting and supporting factors in the implementation of the SAKIP, reviewed based on the policy evaluation theory of William N. Dunn using the variables of: 1). Effectiveness, 2). Efficiency, and 3). Adequacy. The type of research used was qualitative research with purposive sampling method in determining informants of research and the number of selected informants was 5 people, while the data collection techniques were 1). Observations, 2). Interviews, 3) Documentations. Results showed that the Organization Bureau of Central Sulawesi Regional Secretariat had been implementing the Regulation of Central Sulawesi Governor Number 26 of 2011 on the Guidelines for the Preparation of Performance Establishment and Government Agencies Performance Accountability Reporting within the Central Sulawesi Governance, and had carried out its main duties and functions by means of the Apparatus Development Division, particularly the Performance Monitoring and Evaluation Subdivision and Performance Capacity Development Subdivision, but had not run optimally as a whole. The lack of optimality in the regulation implementation was due to the existence of inhibiting factors, namely: 1). The establishment of outcome performance targets that had not yet in part reflected performance as expected, for the difficulty in measuring the success of the outcome performance. 2). Limited human resources, especially of the Apparatus Development Division as the organizer of the SAKIP to interpret the Regulation of Central Sulawesi Governor Number 26 of 2011.